PEMETAAN KERENTANAN COVID-19 DI KABUPATEN KONAWE - Septianto Aldiansyah; Mangapul Parlindungan; Rudi Parluhutan (JURNAL GEOGRAFI, 2021)
Konawe Regency is one of the regencies in Southeast Sulawesi Province that has a high number of confirmed Covid-19 cases. The Covid-19 vulnerability mapping is carried out to facilitate decision making and formulate effective policies to minimize the spread and transmission of the disease. This study aims to examine the parameters that affect the spread and transmission of Covid-19 and the level of susceptibility to Covid-19. The method used is a Chi Square-based Geographic Information System (GIS). The parameters used include Population, Population Density, Elderly Age, Distance from Activity Centers, Distance from Road and Distance from Covid-19 Referral Hospital. The results showed that the population, old age and distance from the Covid-19 referral hospital had an effect on the spread and transmission of Covid-19 with a significance value of 0.000. The most vulnerable areas are in Wawotobi sub-district and Unaaha sub-district with an area of ​​127.68 km2 (5.38%). Areas with a medium level of vulnerability are 1606.57 km2 (67.74%) and low are 637.40 km2 (26.88%). There needs to be an increase in awareness of the use of masks, washing hands, maintaining distance and avoiding crowds because these activities can increase the chance of spreading and transmitting Covid-19.